2021
DOI: 10.3389/fpsyg.2021.653112
|View full text |Cite
|
Sign up to set email alerts
|

Review: Posed vs. Genuine Facial Emotion Recognition and Expression in Autism and Implications for Intervention

Abstract: Different styles of social interaction are one of the core characteristics of autism spectrum disorder (ASD). Social differences among individuals with ASD often include difficulty in discerning the emotions of neurotypical people based on their facial expressions. This review first covers the rich body of literature studying differences in facial emotion recognition (FER) in those with ASD, including behavioral studies and neurological findings. In particular, we highlight subtle emotion recognition and vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…The proposed system was designed with AR, and the system was designed after consulting specialists in the field of childcare. We received a lot of notes and instructions to make the AR system attractive and easy to deal with, and this is consistent with [42], which recommends some ways to teach children facial expressions through images and pictures.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The proposed system was designed with AR, and the system was designed after consulting specialists in the field of childcare. We received a lot of notes and instructions to make the AR system attractive and easy to deal with, and this is consistent with [42], which recommends some ways to teach children facial expressions through images and pictures.…”
Section: Discussionmentioning
confidence: 79%
“…It was noted that the children with autism had neutral facial expressions, while children in the other group interacted, and this appeared from their facial expressions. In [42], which is a recent study, researchers reviewed several studies that studied the relationship of autism with the ability to understand and perceive facial expressions, which indicates the existence of difficulties in this category. It also reviewed some proposals for intervention to teach and improve their ability to understand these expressions, which consisted of images and pictures, and this is what was done in our study, which proved its effectiveness.…”
Section: Related Workmentioning
confidence: 99%
“…Seven selected scenes (5,6,7,11,12,13,14) are experimented with ten-fold cross-validation, respectively. To facilitate visual inspection, we have shown the fusion results in both Table V and Fig.…”
Section: B Performance Of Individual Scenesmentioning
confidence: 99%
“…Studies on facial expression/emotion recognition and ASD have mainly used static images with posed expressions in the literature (e.g., [3] and [4]). Despite the extension to dynamic video with posed facial expression [5], there is still no automated and comprehensive analysis of facial expression in autism, especially in natural settings [6].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding emotional processing, the most common finding is an impairment in facial emotion recognition in individuals with ASD [ 31 , 32 ]. Studies repeatedly showed that patients with ASD exhibit slower reaction times [ 33 ] as well as more incorrect classifications of emotion assignments than typically developing subjects [ 34 36 ]. Moreover, the gaze at the eyes of others is associated with a higher rate of correct answers in emotion recognition and lower symptom severity [ 37 ].…”
Section: Introductionmentioning
confidence: 99%